Digital Dental Models: Is Photogrammetry an Alternative to Dental Extraoral and Intraoral Scanners? - Francesca Zotti; Luca Rosolin; Massimo Bersani; Andrea Poscolere; Davide Pappalardo; Nicoletta Zerman (MDPI AG, 2022)
Background: 3D models are nowadays part of daily clinical practice. Photogrammetry is a brand-new method for transforming small objects into 3D models while keeping their original shape and size. The aim of this study was to evaluate the accuracy, in terms of precision and trueness, of a digital dental model acquired with photogrammetry compared with those obtained using extraoral scanners and intraoral scanners, starting from the same plaster model. Methods: A plaster model was converted into a digital model using photogrammetry, an extraoral scanner and an intraoral scanner. Different references were measured twice at a distance of 30 min for each model, on the digital models using the software Blender and on the plaster model using a calibre. The Interclass Correlation Coefficient was calculated for each pair of measurements. A volumetric analysis was performed by superimposing the digital models. The coefficient of variation was calculated. A two-way ANOVA test was conducted. Results: For each reference, the coefficient of variation was less than 3%, and the two ANOVA tests resulted in a non-significant value in both cases (p > 0.05). The volumetric analysis demonstrated good agreement between the models derived from the different acquisition methods. Conclusions: Photogrammetry seems to be a good method for acquiring digital models starting from a plaster model, all the methods tested seem to be good for obtaining an accurate three-dimensional digital model. Other studies are needed to evaluate clinical efficacy.